The Implementation of Group Work in Enhancing Communicative Activities in Semi-Urban Secondary ESL Classrooms - Harun, Nik Ismail (1998)
This project paper is an investigation on the use of group work in the teaching and learning of English as a Second Language (ESL). It is selected in view of the many advantages of group work and if fully exploited it can be an innovative strategy that can be effectively used in the ESL classrooms. A short survey has been included in this project paper. It attempts to find out the use of group work in the ESL classrooms through the administration of a questionnaire. An analysis of the data showed that the majority of the respondents were receptive towards' the use of group work. Hence, group work can be further exploited as an innovative strategy for the teaching of English. In addition, it proposes five sample lesson plans that include several types of group work which can be used for teachings English for the KBSM Form Two classes. These sample lesson plans attempt to highlight the various types of group work and to give an insight to language teachers using group work in ESL classrooms. Some suggestions and recommendations have also been included with the hope that teachers will give group work its due consideration in the teaching of English.